Joule Heating-Driven sp2-C Domains Modulation in Biomass Carbon for High-Performance Bifunctional Oxygen Electrocatalysis - He, Jiawei; Zhao, Yuying; Li, Yang; Yuan, Qixin; Wu, Yuhan; Wang, Kui; Sun, Kang; Wu, Jingjie; Jiang, Jianchun; Zhang, Baohua; Wang, Liang; Fan, Mengmeng (Nano-Micro Letters, 2025)
Natural biomass-derived carbon material is one promising alternative to traditional graphene-based catalyst for oxygen electrocatalysis. However, their electrocatalytic performance were constrained by the limited modulating strategy. Herein, using N-doped commercial coconut shell-derived activated carbon (AC) as catalyst model, the controllably enhanced sp2-C domains, through an flash Joule heating process, effectively improve the edge defect density and overall graphitization degree of AC catalyst, which tunes the electronic structure of N configurations and accelerates electron transfer, leading to excellent oxygen reduction reaction performance (half-wave potential of 0.884 VRHE, equivalent to commercial 20% Pt/C, with a higher kinetic current density of 5.88 mA cm−2) and oxygen evolution reaction activity (overpotential of 295 mV at 10 mA cm2). In a Zn-air battery, the catalyst shows outstanding cycle stability (over 1200 h) and a peak power density of 121 mW cm−2, surpassing commercial Pt/C and RuO2 catalysts. Density functional theory simulation reveals that the enhanced catalytic activity arises from the axial regulation of local sp2-C domains. This work establishes a robust strategy for sp2-C domain modulation, offering broad applicability in natural biomass-based carbon catalysts for electrocatalysis. Highlights: 1 The flash Joule heating controllably enhanced sp2-domains content in various N-doped natural biomass-based carbon. 2 The axial modulation of sp2-C domains decreased the charge density of pyridinic N and graphitic N configurations resulting into outstanding oxygen electrocatalysis. 3 The assembled Zn-air battery with optimized catalyst achieved an over 1200-h cycle stability with the peak power density of 121 mW cm−2, exceeding the commercial Pt/C + RuO2 catalysts.